2012
DOI: 10.1002/14651858.cd004466.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Incentive spirometry for preventing pulmonary complications after coronary artery bypass graft

Abstract: Our update review suggests there is no evidence of benefit from IS in reducing pulmonary complications and in decreasing the negative effects on pulmonary function in patients undergoing CABG. In view of the modest number of patients studied, methodological shortcomings and poor reporting of the included trials, these results should still be interpreted cautiously. An appropriately powered trial of high methodological rigour is needed to determine if there are patients who may derive benefit from IS following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 66 publications
1
48
2
2
Order By: Relevance
“…In addition, presenting the potential risk factors associated with pulmonary complications ensures the anticipation of complications by determining preventive strategies. In previous studies, for specific surgical groups, like upper abdominal interventions (4), oesophagectomy (5), total knee arthroplasty (6) or coronary artery bypass surgery (7), preoperative risk factors in the development of PPCs were investigated. The European Society of Anaesthesiology (ESA) performed a multinational, multicentre study called PERISCOPE (Prospective Evaluation of a Risk Score for postoperative pulmonary Complications in Europe), which our clinic also attended.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, presenting the potential risk factors associated with pulmonary complications ensures the anticipation of complications by determining preventive strategies. In previous studies, for specific surgical groups, like upper abdominal interventions (4), oesophagectomy (5), total knee arthroplasty (6) or coronary artery bypass surgery (7), preoperative risk factors in the development of PPCs were investigated. The European Society of Anaesthesiology (ESA) performed a multinational, multicentre study called PERISCOPE (Prospective Evaluation of a Risk Score for postoperative pulmonary Complications in Europe), which our clinic also attended.…”
Section: Introductionmentioning
confidence: 99%
“…63 The two most recent Cochrane reviews of incentive spirometry for PPC prevention following upper abdominal surgery and cardiac/thoracic surgery also concluded that there is "no evidence" of benefit in either group. 64,65 These findings are supported by the work of Agostini et al 66 Finally, a recent detailed systematic review by Carvalho and co-workers evaluated 30 studies that used incentive spirometry after upper abdominal surgery (n ϭ 14) and cardiac/thoracic surgery (n ϭ 16). These authors painstakingly reviewed the study designs, interventions, measured outcomes, and methodological rigor of each trial.…”
Section: Incentive Spirometrymentioning
confidence: 72%
“…[90][91][92][93] Similarly, IPPB has not shown to improve postoperative outcomes. 65,94 In both instances the data are not available to support routine use.…”
Section: Other Techniquesmentioning
confidence: 99%
“…With reference to nonpressure related DBE, the effect of IS was compared to other prophylactic physiotherapy tech niques on postoperative pulmonary complications (PPC) following CABG in a Cochrane review (Freitas et al 2007) (level 1a evidence). A total of four randomised controlled trials met the inclusion criteria for this review.…”
Section: Discussionmentioning
confidence: 99%
“…The reviewers found no differences in PPC when using IS or a pressure device such as IPPB for patients after CABG surgery. Worse pulmonary function and arterial oxygen levels were reported with the use of IS when compared with pressure devices (Freitas et al, 2007). Even though the evidence is contradictory in nature regarding the use of chest clearance techniques such as DBE, IS, blowbottle and IPPB postoperatively, patients who undergo CABG surgery have significant pulmonary dysfunction four days post operatively which can persist up to four months following surgery (Westerdahl et al, 2003).…”
Section: Discussionmentioning
confidence: 99%